Clinical Features, Management, and Prognosis of an International Series of 161 Patients With Limited-Stage Diffuse Large B-Cell Lymphoma of the Bone (the IELSG-14 Study). (24th February 2014) - Bruno Ventre, Marta; Ferreri, Andrés J.M.; Gospodarowicz, Mary; Govi, Silvia; Messina, Carlo; Porter, David; Radford, John; Heo, Dae Seog; Park, Yeon; Martinelli, Giovanni; Taylor, Emma; Lucraft, Helen; et al.
Abstract : Learning Objectives: Compare outcomes in patients with diffuse large B-cell lymphoma of the bone treated with different modalities. Compare relapse rates and relapse sites in patients with diffuse large B-cell lymphoma of the bone treated with different modalities. Introduction: The clinical features, management, and prognosis of stage I–II diffuse large B-cell lymphoma of the bone (PB-DLBCL) included in an international database of 499 lymphoma patients with skeletal involvement were reviewed. Methods: HIV-negative patients ( n = 161) with diffuse large B-cell lymphoma of the bone (PB-DLBCL) after complete staging workup were considered. The primary objective of this study was to identify the most effective treatment modality; the secondary objectives were to define the contribution of irradiation fields and doses and the pattern of relapse. Results: Median age was 55 years (range, 18–99 years), with a male/female ratio of 1:2; 141 (87%) patients had stage I, 14 (9%) had B symptoms, 37 (23%) had bulky lesion, 54 (33%) showed elevated lactate dehydrogenase serum levels, and 25 (15%) had fracture. Thirteen (8%) patients received chemotherapy alone, 23 (14%) received radiotherapy alone, and 125 (78%) received both treatments. The response to the first-line treatment was complete in 131 of 152 assessed patients (complete response rate, 86%; 95% confidence interval [CI], 81%–91%) and partial in 7, with an overall response rate of 91% (95% CI, 87%–95%). At a median follow-up of 54 months (range, 3–218), 107 (67%) patients remained relapse-free, with a 5-year progression-free survival of 68% (SE: 4). Four (2.5%) patients had meningeal relapse; 119 patients were alive (113 disease-free), with a 5-year overall survival of 75% (SE: 4). Patients managed with primary chemotherapy, whether followed by radiotherapy or not, had a significantly better outcome than patients treated with primary radiotherapy, whether followed by chemotherapy or not. The addition of consolidative radiotherapy after primary chemotherapy was not associated with improved outcome; doses >36 Gy and the irradiation of the whole affected bone were not associated with better outcome. Conclusion: Patients with PB-DLBCL exhibit a favorable prognosis when treated with primary anthracycline-based chemotherapy whether followed by radiotherapy or not. In patients treated with chemoradiotherapy, the use of larger radiation fields and doses is not associated with better outcome. Central nervous system dissemination is a rare event in PB-DLBCL patients. Abstract : The authors reviewed the clinical features, management, and prognosis of 161 patients with stage I–II diffuse large B-cell lymphoma of the bone. Patients managed with primary chemotherapy had a significantly better outcome than patients treated with primary radiotherapy. The addition of consolidative radiotherapy after primary chemotherapy was not associated with improved outcome.